Machiavelli and The Federalist. - Hawley, Michael C. (Tufts Archival Research Center, 2005)
The Federalist Papers are considered by many to be the most revealing guide to the thought underpinning the United States Constitution. Written chiefly by James Madison and Alexander Hamilton (with a small contribution by John Jay) under the pseudonym of Publius, The Federalist advocated for the ratification of the new Constitution. Niccolò Machiavelli was a Renaissance republican thinker, whose insights into politics in The Prince and Discourses on Livy profoundly shaped subsequent political thought. Despite the fact that the American founding constitutes a seminal moment in the history of republicanism, few scholars have sought to use the thought of the great Florentine republican to enlighten us about it. This thesis explores the complicated relationship between Alexander Hamilton and James Madison as expressed in The Federalist through the interpretive prism of Machiavelli. Although joined temporarily in a united front to secure the ratification of the new Constitution, Madison and Hamilton would go on to become bitter political enemies. This thesis argues that the latent tensions between the Virginian and the New Yorker can be discerned even in The Federalist. Using Machiavelli's thought as a guide, the thesis tracks a dialogue between Madison and Hamilton across four themes: human nature, the proper character of the American republic, issues of restraint and empowerment, and republican virtue. Ultimately, the views of Madison and Hamilton achieve an imperfect synthesis in The Federalist, a partial reconciliation that can be better understood through the thought of Machiavelli.